Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Klinik Bethesda - Sihombing, Ida Cristiany; Luturlean, Bachruddin Saleh (eProceedings of Management, 2024)
Bethesda Clinic is a healthcare facility located in Garut, West Java. To enhance the performance of its staff, theclinic must foster motivation and a positive work environment. This approach aims to ensure that work activitiesalign with predetermined objectives. Consequently, the goal of this research is to examine and analyze the impact ofwork motivation and the work environment on employee performance at Bethesda Clinic in Garut. This researchemploys a quantitative method, with primary data collected using a saturated sampling technique from a sampleof 50 employees at Bethesda Clinic in Garut. The data was then analyzed through descriptive analysis andmultiple linear regression. The descriptive analysis results indicate that both motivation and the work environmentare rated as good. The study findings reveal that motivation and the work environment partially andsimultaneously affect employee performance by 55.8%, while the remaining 44.2% is influenced by other factors notcovered in this study.Keywords-motivation, work environment, employee performance